Risk Factors and Etiologies of Ischemic Stroke in Young Adults: A Hospital-based Study in Bangladesh (BIRDEM Medical Journal, 2018)
Background: Stroke is an important cause of disability among adults and is one of the leading causes of death worldwide. Strokes in young adults can have a significant impact on the affected individuals, their families and societies in general as the affected patients are in the economically productive period of their lives.This study was aimed to find out the demographic profile and explore the associated risk factors of the first-ever ischemic stroke of young adults.Methods: This retrospective study reviewed the records of 64 patients, age 18-49 years, ischemic stroke patients consecutively admitted in the Neurology department, BIRDEM General Hospital during the period January 2016 to June 2017. Study variables included hematological and biochemistry investigations and radiological and imaging findings. Stroke sub-typing was done following to TOAST criteria. Data of follow-up data at 3 month were also included. Data were expressed as number (percent) and managed by SPSS for Windows Version 15.Results: Of the 634 patients diagnosed as acute ischemic stroke 64 (9.90%) were in the 18-49 (yr) age range and the majority (55.4%) were male. Stroke was more common (47 out of 54) among the 31-49 years category as compare with the